(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Technology and automation play a key role in modern management, ensuring efficiency, accuracy and speed of information processing. With the rapid development of digital solutions, companies are increasingly turning to automation of routine processes, which frees up time for strategic planning and making more informed decisions. The implementation of project management systems, CRM and ERP systems helps to simplify communication between departments, improve resource management and improve the level of customer service.